2016
DOI: 10.1109/tpwrd.2015.2509644
|View full text |Cite
|
Sign up to set email alerts
|

Interoperability Performance Assessment of Multivendor IEC61850 Process Bus

Abstract: Abstract--Substations are increasingly reliant on devices compatible with IEC61850 standards. However, the conformity of a devicewith the standards does not necessarily guarantee interoperability with devices from different manufacturers. The use of devices compatible with IEC61850 standards presents a challenge to many system integrators, especially due to lack of familiarity with features such as Generic Object Oriented Substation Event (GOOSE), reporting, sample values and the need for system redundancy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
(11 reference statements)
0
8
0
5
Order By: Relevance
“…The results suggest that the protection passed the tests and that several aspects of the IEC 61850 standard may be very conservative. In [18], the authors highlighted the need to validate the compatibility and performance of MUs and IEDs; therefore, they test distance protection considering communications redundancy.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that the protection passed the tests and that several aspects of the IEC 61850 standard may be very conservative. In [18], the authors highlighted the need to validate the compatibility and performance of MUs and IEDs; therefore, they test distance protection considering communications redundancy.…”
Section: Introductionmentioning
confidence: 99%
“…Huu‐Dung [6] have assessed and evaluated the HSR network performance on process level by OPNET simulation tool. Xi and Peter [7] designed a test platform in the lab for a process bus with PRP to access the IEDs interoperbility performance from different suppliers. The authors of [7, 8] present a substation with the implementation of HSR protocol and PRP, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Xi and Peter [7] designed a test platform in the lab for a process bus with PRP to access the IEDs interoperbility performance from different suppliers. The authors of [7, 8] present a substation with the implementation of HSR protocol and PRP, respectively. Recently, Scottish Power Energy Networks (SPENs’) has considered to deploy a real live full digital substation for a 275 kV substation in Scotland through UK government Ofgem’ Network Innovation Competition (NIC) funded Future Intelligent Transmission Network Substation (FITNESS) project [9].…”
Section: Introductionmentioning
confidence: 99%
“…the IEC 61850‐9‐2 Sampled Values (SV), IEC 61850‐8‐1 Generic Object Oriented Substation Events (GOOSE) and Manufacturing Message Specification (MMS). Many studies have been carried out to test the interoperability of SV between Merging Units (MUs) and IEDs [1–3], GOOSE between IEDs [4, 5], and MMS between substation Human Machine Interfaces (HMIs) and IEDs [6, 7]. In the studies, several interoperability issues have been reported [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, certain SCL tools cannot properly interpret the SCL files from third party tools, resulting in unsuccessful GOOSE subscriptions. Further studies have been carried out to evaluate interoperability performance under various conditions, such as SV/GOOSE delays under different background traffics [1, 5], impacts of SV packet loss on IEDs [10], SV delay with network redundancy protocols and impacts of time synchronisation loss on MUs and IEDs [3, 11].…”
Section: Introductionmentioning
confidence: 99%